Malaysia's development success story: critical responses in contemporary Malaysian novels in English - Zainal, Zainor Izat (Canadian Center of Science and Education, 2014)
Malaysia is often hailed as a development success story. However, one criticism of this success story is the over-emphasis on the ideology of economic and capitalist growth by the state in its setting, determining and directing of development. This paper looks into some of the most interesting and critical reflections on development. Representing prominent voices in Malaysian literature in English, K. S. Maniam, Chuah Guat Eng and Yang-May Ooi delve into Malaysia’s development success story through Between Lives (2003), Days of Change (2010) and The Flame Tree (1998), respectively. Through textual analysis, I examine how these writers treat the state’s prevailing ideology of development. Through their creative responses to the rapid development that has occurred in Malaysia, Maniam, Chuah and Ooi offer individual expression and powerful critiques of development, not merely reflecting on the ideology of economic and capitalist growth but also illustrating different perspectives on development based on notions of social justice, democracy and cultural sustainability. That is not to say that they reject development. On the contrary, they acknowledge that development is part and parcel of social, economic and political processes. However, through their treatment of development, they bring to light other equally important issues, thus emphasizing the flaws in adopting a development model that is essentially based on economic and capitalist growth.